Turkey’s Foreign Policy in the Post-Bipolar System of Coordinate - P. V. Shlykov (Международная аналитика, 2021)
Turkey's foreign policy in the ﬁrst decade after the collapse of the bipolar system retained features of its continuity in comparison with the Cold War: the Kemalist principles of laicism and the choice in favor of further Westernization, with its orientation towards cooperation with the EU and Euro-Atlantic structures remained ﬁrmly in place. However, the post-bipolar period demonstrated a signiﬁcant change in Turkey's foreign policy. The existing explanations for this phenomenon often start either from the appeal to the Islamic identity of the Justice and Development Party as the main reason for the changes, or from the approaches that prioritize Turkey's economic interests and emphasize Turkey's attempts to strengthen economic interdependence with neighbors in the region. Given the increasing complexity of the domestic and foreign policy nexus and the increasingly ﬂuid characteristics of the international environment, it seems that an analysis of Turkish foreign policy in the post-bipolar period requires an alternative conceptual and methodological approach that allows the changes in Turkey's foreign policy to be viewed along three dimensions. In this article, the author resorts to just such an approach. It includes the study of domestic policy, the international context and the transformation of the ideological and institutional support of foreign policy. This approach makes it possible to explain the logic of Turkey's «sudden» reorientation from cooperation with the EU and Western countries in general to attempts to consolidate its leading role in the Middle East and establish itself as a regional hegemon in relation to situational alliances with various state and non-state actors in the broader international context.